Secured telemedicine of medical imaging based on dual robust watermarking - Mata-Mendoza, David; Cedillo-Hernandez, Manuel; Garcia-Ugalde, Francisco; Cedillo-Hernandez, Antonio; Nakano-Miyatake, Mariko; Perez-Meana, Hector (The Visual computer, 2022)
Medical information management has progressed in the last few years because of the advances in information technologies. Nowadays, it is possible to share medical images among specialists geographically distant to interpret, discuss, and get improved diagnostics. However, any alteration of transmitted image metadata may lead to issues related to information security, such as detachment and authentication. Detachment refers to link the data of an electronic patient record to an incorrect medical image, while authentication aims to identify the image source. These security problems are critical as they may cause the loss of sensitive data or wrong medical diagnoses. Digital watermarking is an emerging technique that faces these security problems as it allows to embed the metadata directly into the medical image. This paper proposes a hybrid and robust watermarking technique to prevent detachment and authenticate medical images. The quantization index modulation algorithm under dither modulation in conjunction with forwarding error correction is used to embed relevant metadata as a robust-imperceptible watermarking to avoid detachment. The visible-imperceptible watermarking paradigm, whose use is an innovation in medical images, is applied to insert a second watermark in the spatial domain to perform authentication. The experimental results show the contribution of the proposed scheme and its efficiency regarding robustness and imperceptibility.